2009
DOI: 10.1037/a0015021
|View full text |Cite
|
Sign up to set email alerts
|

Optimal integration of auditory and vibrotactile information for judgments of temporal order.

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Stimuli were auditory, vibrotactile, or both. The temporal profiles of vibrotactile stimuli were manipulated, producing three levels of TOJ precision. In bimodal conditions, the asynchrony between the two unimodal stimuli comprising a bimodal stimulus was also manipulated to determine the weight given to touch. Unimodal data were used to predict bimodal performance on two measures: judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
1
21
1
Order By: Relevance
“…Our use of two concurrent stimuli, however, may have acted to decorrelate to some extent, the timing information at each ear, making the extraction of ITD cues for each stimulus unreliable (see Lee et al 2009;Rakerd and Hartmann 2010, but see also Schwartz et al 2012) and causing a down-weighting of the ITD cue relative to the ILD cue. This would be consistent with recent models of optimal cue integration in a variety of sensory systems which embody a Bayesian or BKalman filter^approach to optimize fusion of multiple cues that may vary in reliability (Ley et al 2009;Wozny and Shams 2011).…”
Section: Summary Of Findings In Spatial Coordinatessupporting
confidence: 85%
“…Our use of two concurrent stimuli, however, may have acted to decorrelate to some extent, the timing information at each ear, making the extraction of ITD cues for each stimulus unreliable (see Lee et al 2009;Rakerd and Hartmann 2010, but see also Schwartz et al 2012) and causing a down-weighting of the ITD cue relative to the ILD cue. This would be consistent with recent models of optimal cue integration in a variety of sensory systems which embody a Bayesian or BKalman filter^approach to optimize fusion of multiple cues that may vary in reliability (Ley et al 2009;Wozny and Shams 2011).…”
Section: Summary Of Findings In Spatial Coordinatessupporting
confidence: 85%
“…This approach is commonly used (e.g. Ernst & Banks, 2002;Ley, Haggard, & Yarrow, 2009) in order to estimate the weight being assigned to each sensory modality, and thus provide a further means of assessing the predictions of weighted integration models.…”
Section: Discussionmentioning
confidence: 99%
“…They found that abrupt sounds attract the onsets of lights if presented within a time window of~±200 ms from the flash. Using the same paradigm, temporal ventriloquism has also been demonstrated between the visual and tactile modalities, in which taps capture the onsets of visual stimuli (Keetels & Vroomen, 2008a, 2008b, and between the auditory and tactile modalities (Ley, Haggard & Yarrow, 2009;Wilson, Reed & Braida, 2009). …”
Section: Temporal Ventriloquism: Immediate Effectmentioning
confidence: 96%
“…The Bayesian approach has also been adopted to understand temporal ventriloquism (Burr et al, 2009;Hartcher-O'Brien & Alais, 2011;Ley et al, 2009;Shi et al, 2010). Interestingly, different from the findings in spatial ventriloquism, all these studies report that the quantitative fit (dominance of auditory over visual in temporal perception) was less perfect than predicted by maximum likelihood estimation, although temporal localization of audiovisual stimuli was better than for the visual sense alone.…”
Section: Bayesian Approachesmentioning
confidence: 99%